Associations between elevated pre‐treatment serum cytokines and peripheral blood cellular markers of immunosuppression in patients with lymphoma. Issue 8 (1st June 2017) - Binder, Moritz; O'Byrne, Megan M.; Maurer, Matthew J.; Ansell, Stephen; Feldman, Andrew L.; Cerhan, James; Novak, Anne; Porrata, Luis F.; Markovic, Svetomir; Link, Brian K.; Witzig, Thomas E.
Abstract: Higher ratios of the pre‐treatment peripheral blood absolute lymphocyte (ALC) to absolute monocyte counts (AMC) are associated with improved outcomes in lymphoma. Conversely, elevated pre‐treatment serum cytokines are associated with inferior outcomes. The relationship between pre‐treatment serum cytokines and ALC/AMC ratios remains unknown. We studied twelve serum cytokines and the ALC/AMC ratios in 390 patients with untreated diffuse large B‐cell, follicular, mantle cell, T‐cell, and Hodgkin lymphoma. Different pre‐treatment serum cytokine concentrations correlated with ALC, AMC, and ALC/AMC ratios depending on the lymphoma type. In the entire cohort ( n = 390) lower ALC/AMC ratios modestly correlated with higher IL‐2R ( r = −0.36), IL‐12 ( r = −0.17), IP‐10 ( r = −0.23), and MIG ( r = −0.32) concentrations ( p < 0.001). Elevated IL‐2R was independently associated with suppressed ALC (OR 2.69, 95% CI 1.77–4.07, p < 0.001), elevated AMC (OR 2.05, 95% CI 1.34–3.14, p < 0.001), and suppressed ALC/AMC ratios (OR 3.51, 95% CI 2.31–5.34, p < 0.001). Both elevated IL‐2R (HR 2.27, 95% CI 1.48–3.49, p < 0.001) and suppressed ALC/AMC ratios (HR 1.53, 95% CI 1.03–2.28, p = 0.037) were independently associated with inferior overall survival. These data support the notion that elevated serum cytokines are immunosuppressive and provide further rationale to target the tumor microenvironment for therapeutic benefit.